The growing global burden of end stage renal disease (ESRD) - (:unkn) unknown (My University, 2005)
The incidence and prevalence of renal replacement therapies (RRT) is increasing worldwide. As well as being a large and growing clinical problem, it consumes a considerable proportion of health care resources in both developed and developing countries. Ideally, every ESRD patient should have access to dialysis. The reality is that there is not enough money for healthcare in the developing world, particularly for expensive and chronic treatment such as RRT. Efforts should be made to have the cost of peritoneal dialysis fluids reduced and to increase the availability of transplantation.
Keywords: Costs; End stage renal disease; Epidemiology